Measuring the effects of conventional and unconventional monetary policy in the euro area - Juho Anttila (Bank of Finland, 2018)
I estimate the effects of conventional and unconventional monetary policy in the euro area by using a factor-augmented vector autoregression.I complement the standard monetary policy analysis using the short rate with models where the shadow rates by Kortela (2016) and Wu and Xia (2017) are used as proxies for unconventional monetary policy. I quantify the effects of unanticipated monetary policy shocks using impulse response functions, forecast-error variance decompositions, and counterfactual simulations. The results indicate that unconventional monetary policy shocks have similar, expansionary effects on the economy as conventional monetary policy shocks.
URN:NBN:fi:bof-201805291584
Keywords: E43; E44; E52; E58; 330